Mucoadhesion and Mucopenetration of Cannabidiol (CBD)-Loaded Mesoporous Carrier Systems for Buccal Drug Delivery - Ulrike Söpper; Anja Hoffmann; Rolf Daniels (Scientia Pharmaceutica, 2021)
Transmucosal drug delivery represents a promising noninvasive option when drugs are employed which have a low oral bioavailability like CBD. However, this concept can only be successful as long as the formulation provides sufficient buccal retention and mucosal penetration. In this study, mucoadhesive carrier systems were evaluated consisting of CBD-loaded silica (Aeroperl 300) carriers, mucoadhesive polymers (Hypromellose (HPMC), chitosan and carbomer) and propylene glycol as a penetration enhancer. Mucoadhesive effect, drug release and penetration ability were evaluated for each carrier system. The results show that the addition of HPMC and carbomer substantially improve mucoadhesion compared to pure CBD, with an increase of 16-fold and 20-fold, respectively. However, due to their strong swelling, HPMC and carbomer hinder the penetration of CBD and rely on co-administration of propylene glycol as an enhancer to achieve sufficient mucosal absorption. Chitosan, on the other hand, achieves an 8-fold increase in mucoadhesion and enhances the amount of CBD absorbed by three times compared to pure CBD. Thus, chitosan represents a promising polymer to combine both effects. Considering the results, the development of silica-based buccal drug delivery systems is a promising approach for the effective delivery of CBD.